New approach to weight‐of‐evidence assessment of ecotoxicological effects in regulatory decision‐making. (19th May 2017) - Hall, A Tilghman; Belanger, Scott E; Guiney, Pat D; Galay‐Burgos, Malyka; Maack, Gerd; Stubblefield, William; Martin, Olwenn
ABSTRACT: Ecological risk assessments and risk management decisions are only as sound as the underlying information and processes to integrate them. It is important to develop transparent and reproducible procedures a priori to integrate often‐heterogeneous evidence. Current weight‐of‐evidence (WoE) approaches for effects or hazard assessment tend to conflate aspects of the assessment of the quality of the data with the strength of the body of evidence as a whole. We take forward recent developments in the critical appraisal of the reliability and relevance of individual ecotoxicological studies as part of the effect or hazard assessment of prospective risk assessments and propose a streamlined WoE approach. The aim is to avoid overlap and double accounting of criteria used in reliability and relevance with that used in current WoE methods. The protection goals, problem formulation, and evaluation process need to be clarified at the outset. The data are first integrated according to lines of evidence (LoEs), typically mechanistic insights (e.g., cellular, subcellular, genomic), in vivo experiments, and higher‐tiered field or observational studies. Data are then plotted on the basis of both relevance and reliability scores or categories. This graphical approach provides a means to visually assess and communicate the credibility (reliability and relevance of available individual studies), quantity, diversity, and consistency of the evidence. In addition, the external coherence of the body of evidence needs to be considered. The final step in the process is to derive an expression of the confidence in the conclusions of integrating the information considering these 5 aspects in the context of remaining uncertainties. We suggest that this streamlined approach to WoE for the effects or hazard characterization should facilitate reproducible and transparent assessments of data across different regulatory requirements. Integr Environ Assess Manag 2017;13:573–579. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: Relevance assessment of ecotoxicity studies is required to ensure appropriate use in hazard and risk assessment of chemicals.